Improvements in error-monitoring and symptoms following low-frequency rTMS of dorsal anterior cingulate cortex in obsessive compulsive disorder; a randomized, sham-controlled study - Meek, Benjamin P.; Fotros, Aryandokht; Abo Aoun, Mohamed; Modirrousta, Mandana (Brain and cognition, 2021)
•rTMS over dACC enhances rapid error monitoring in OCD.•OCD symptom severity improved by dACC neuromodulation.•Low-frequency rTMS may reduce dACC hyperactivity seen in OCD.•Results reinforce the link between error monitoring impairment and OCD pathology. Action monitoring deficit is a core underlying characteristic and endophenotype of Obsessive Compulsive Disorder (OCD). Dorsal anterior cingulate cortex (dACC) is heavily involved in error monitoring and cognitive control, and the hyperactivity in this region is associated with OCD symptom severity. This study aimed to test whether low frequency (LF) repetitive transcranial magnetic stimulation (rTMS) targeting dACC improves both error-monitoring performance and OCD symptoms in a randomized, sham-controlled, double-blind trial design. 20 OCD patients were randomly assigned to receive 20 sessions of Active (n = 10) or Sham (n = 10) rTMS administered twice-daily. Error-monitoring performance and symptom severity were measured pre- and post-treatment using Erikson Flanker tasks and the Yale-Brown Obsessive Compulsive Scale (Y-BOCS), with three month symptom follow-up. Following active—but not sham—rTMS, patients showed improved response time for incongruent stimuli, trials following a correct response, and for reporting and correcting errors. Significant OCD symptom improvement was observed at one-month follow-up for patients who received Active (28.0% reduction) but not Sham (11.7% reduction) stimulation. In OCD patients, LF rTMS of the dACC can simultaneously improve on-line adjustment of behaviour—by enhancing the capacity for rapid error monitoring—and clinical symptoms, suggesting a link between error monitoring impairment and OCD pathophysiology.